2021
DOI: 10.31616/asj.2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

Long versus Short Segment Instrumentation in Osteoporotic Thoracolumbar Vertebral Fracture

Abstract: This study aimed to compare clinical and radiological data and rate of mechanical complications in elderly patients treated with short segment (SSS) or long segment stabilization (LSS) for thoracolumbar junction osteoporotic vertebral fractures (OVFs). Overview of Literature: A fervent debate is now focused on the treatment of OVF using SSS or LSS. High rate of complications is associated with pedicle screw fixation because of poor bone quality. Methods: Patients over 65 years old with a T-score of <−2.5, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
2
25
0
3
Order By: Relevance
“…Further, most spine surgeons are more familiar with posterior approach. In biomechanically, LF with two or more levels above and below the fracture is a better choice for thoracolumbar burst fracture, which can provide greater mechanical stiffness and reduce likelihood of segmental collapse and implant failure [4,17]. However, except disruption of spinal motion segments, LF is correlated with more severe surgical invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, most spine surgeons are more familiar with posterior approach. In biomechanically, LF with two or more levels above and below the fracture is a better choice for thoracolumbar burst fracture, which can provide greater mechanical stiffness and reduce likelihood of segmental collapse and implant failure [4,17]. However, except disruption of spinal motion segments, LF is correlated with more severe surgical invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Schulze et al [21] reported signi cant migration of pedicle screws following xation of osteoporotic vertebrae placed under exion/extension cyclic loading, and the anchoring effect holding the screw in place was decreased in osteoporotic cases. Although intermediate pedicle screws were used in the fractured vertebra, signi cant kyphotic correction loss and mechanical failure were observed in cases with osteoporotic thoracolumbar fracture [4]. In addition, the intravertebral area of osteoporotic burst fracture enlarged by positional or instrumental reduction is nearly empty, and such insu cient anterior column support may not endure vertical physiological strength with stand-alone posterior pedicle construct, even LF construct was used [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank the Author for their interest in our manuscript [ 1 ], and we would like to reply to their comments:…”
mentioning
confidence: 99%
“…We have read the article by Girardo et al [ 1 ] entitled “Long versus short segment instrumentation in osteoporotic thoracolumbar vertebral fracture” with great interest and congratulate the authors for this thought-provoking topic of interest; however, there are few pertinent queries that need to be addressed:…”
mentioning
confidence: 99%